Characterization of Cr/Ag Bi-Layer thin Metal Contacts Sputter Deposited on N-Type Si Semiconductor - Al, Ahmad Hadi; Pauzi, Nurul Syafiqah (International Journal of Engineering and Technology, 2018)
Good electrical conductivity of metal contacts on semiconductor are very crucial in determining quality of the energy conversion efficiency. This paper reports on the Cr/Ag thin metal contacts properties sputter deposited on n-type Si. The metal contacts were characterized based on the morphological and electrical properties. The surface morphology of metal contacts was characterized by using atomic force microscope (AFM) and resulted in increment of the surface roughness from 1.35 nm to 9.21 nm at the thickness of 20 nm to 100 nm. The electrical characteristics were characterized by using four-point probe system. From the measurement, the lowest electrical resistivity was measured as 1.19 Ã— 10-6 W-cm at Ag thickness of 100 nm. Whereas the electrical conductivity of the thin metal contact was obtained as 8.40 Ã— 105 W-cm-1 at Ag thickness of 100 nm. From the analysis, it is clearly shown that as the Ag thin metal thickness gets thicker, the surface roughness gets rougher thus resulting in the improvement of the electrical characteristics of the Si/Cr/Ag contacts.